PERANAN POLITIK HUKUM DALAM UPAYA KODIFIKASI DAN UNIFIKASI HUKUM GUNA PEMBANGUNAN HUKUM NASIONAL YANG SESUAI DENGAN PANCASILA SERTA PRINSIP KEBHINEKAAN DI INDONESIA - Mahanani, Anajeng Esri Edhi (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2017)
This article aims to analyze the political role of the law in an effort to codification and unification of the law for the development of national law in accordance with Pancasila and the diversity principle of Indonesia. The development of national law requires the codification of a new law by replacing and removing colonial laws which is still up to now. This research is a normative prescriptive research. The result of the discussion concludes that the codification and unification needed in Indonesia with its diversity condition is partial and open codification and unification.